SURVEI SARANA DAN PRASARANA PENJASORKES DI SLTP NEGERI SE-KABUPATEN BATANG TAHUN AJARAN 2012-2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this thesis to Know Penjasorkes availability of facilities and infrastructure that exist in SMP as Batang year 2012/2013. Data was collected through observations, interviews and documentation. Data analysis using descriptive analysis, describing the existence Penjasorkes infrastructure that is in Junior High School as Batang. Research results indicate that the availability of facilities and infrastructure in the Junior High School Penjasorkes a Batangadalah District as follows: Branch Football sports average is (54.17%) either category, (22.22%) category enough, (23.61% ) less category, Volleyball average is (65.62%) either category, (30.20%) category enough, (4.17%) less category, Basketball average is (51.39%) category well, (25.69%) category enough, (22.91%) less category, Athletics average is (53.87%) either category, (7.17%) categories enough, (38.95%) category less, Gymnastics average is (47.91%) either category, (10.41%) category enough, (41.67%) less category. The conclusion of this study is that the availability of facilities and infrastructure in the Junior High School Penjasorkes as Batang is good.